Stan Brakhage : filmmaker - James, David E., 1945- (Philadelphia : Temple University Press, 2005)
The art and legacy of a towering figure in the independent film movement.
Introduction : Stan Brakhage : the activity of his nature / David E. James -- Stan Brakhage / Parker Tyler -- Brakhage, Breer, Menken : the pure poets of cinema / Jonas Mekas -- Brakhage and Rilke / Jerome Hill -- On the art of vision / Robert Kelly -- The first time I heard the word "Brakhage" / Edward Dorn -- Camera lucida/camera obscura / Annette Michelson -- Brakhage memoir / James Tenney -- Amateurs in the industry town : Stan Brakhage and Andy Warhol in Los Angeles / David E. James -- It is painting / Carolee Schneemann -- Brakhage : poesis / R. Bruce Elder -- Recollections of Stan Brakhage / Jonas Mekas -- The Roman numeral series / Nicky Hamlyn -- Letter re : Stan / Bruce Baillie -- Stan Brakhage, agrimoniac / Craig Dworkin -- Brakhage package / Chick Strand -- Brakhage's Faustian psychodrama / P. Adams Sitney -- Stan Brakhage : American visionary / Willie Varela -- Brakhage's occasions : figure, subjectivity, and avant-garde politics / Tyrus Miler -- Notes on sincerity and irony / Abigail Child -- Becoming dark with excess of light : the Vancouver Island films / Paul Arthur -- As I am writing this today / Phil Solomon.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Brakhage, Stan -- Criticism and interpretation; Brakhage, Stan -- Criticism and interpretation; Brakhage, Stan; Brakhage, Stan; Motion picture producers and directors -- Biography; Producteurs et réalisateurs de cinéma -- Biographies; PERFORMING ARTS -- Film & Video -- Direction & Production; PERFORMING ARTS -- Film & Video -- General; Motion picture producers and directors; Films; Avant-garde.; Biographies; Criticism, interpretation, etc